A new rhamphorhynchid pterosaur (Pterosauria) from Jurassic deposits of Liaoning Province, China - Lü, Junchang; Pu, Hanyong; Xu, Li; Wei, Xuefang; Chang, Huali; Kundrát, Martin (Zootaxa, 2015)
Compared to pterosaurs from the Early Cretaceous from China, Late Jurassic pterosaurs are relatively rare. A new rhamphorhynchid pterosaur, Orientognathus chaoyngensis gen. et sp. nov., is erected based on an incomplete skeleton from the Upper Jurassic Tuchengzi Formation of Chaoyang, Liaoning Province, China. It is identified by the following characters: the toothless tip of the lower jaw is slightly pointed; the length ratio of wing metacarpal to humerus is 0.38, the ulna is shorter than each wing phalanx and the tibia is nearly equal to femur in length. A phylogenetic analysis recovers Orientognathus chaoyngensis as a rhamphorhynchid pterosaur. Orientognathus chaoyngensis is perhaps the youngest Jurassic pterosaur from western Liaoning Province of China.